PCI for Chronic Total Occlusions with Distal Diffuse Disease: Stent Alone vs. Stent plus Drug Balloon - Xinyi Yan; Xinchen Gao; Yingying Hu; Jianlei Cao; Wei Zhang; Yi Lu; Jia Zhou; Qingqing Wu; Xiaorong Hu (International Journal of Cardiology: Heart & Vasculature)
Background: Chronic total occlusion (CTO) of coronary arteries is a significant challenge in percutaneous coronary intervention (PCI). Despite successful revascularization, patients often develop diffuse coronary lesions, increasing the risk of restenosis and necessitating complex stent strategies. Objective: This study aimed to compare the clinical outcomes of drug-eluting stents (DES) combined with drug-coated balloon (DCB) angioplasty versus DES-only treatment in patients with revascularized CTO and diffuse coronary artery disease. Methods: Patients with successfully revascularized CTO and diffuse lesions were divided into DES-only (n = 191) and DES plus DCB (n = 100) groups. The primary endpoint was major adverse cardiovascular events (MACE), including all-cause death, cardiac death, stroke, and revascularization. The secondary endpoint was the rate of cardiovascular-related hospitalization. Symptom improvement was evaluated using the Canadian Cardiovascular Society (CCS) classification. Results: At 24-month follow-up, the DES plus DCB group had significantly lower MACE incidence (26.00 % vs. 41.36 %, P = 0.008) and cardiovascular-related hospitalization (20.00 % vs. 36.65 %, P = 0.005) compared to the DES-only group. CCS classification improved more significantly in the DES plus DCB group (P < 0.001). Multivariate Cox regression identified DES plus DCB as an independent protective factor against MACE (HR, 0.57; 95 % CI, 0.33–0.99; P = 0.046). Conclusion: In patients with revascularized CTO and diffuse coronary artery disease, the combined DES plus DCB strategy was associated with a lower incidence of MACE and reduced cardiovascular-related hospitalization compared to DES-only treatment. This approach may represent a superior therapeutic option for managing complex coronary lesions.